2022
DOI: 10.3390/medicina58060696
|View full text |Cite
|
Sign up to set email alerts
|

Knee Arthrodesis Affects Gait Kinematics More in the Ankle Than in the Hip Joint

Abstract: Background and Objectives: No gold standard exists for treating persistent periprosthetic knee infections. Knee arthrodesis represents one treatment concept for extensive bone defects and extensor system insufficiencies. It has already been shown that knee arthrodesis leads to a significant reduction in one’s quality of life. The aim of this survey was to assess the influence of knee arthrodesis on the neighboring joints on the basis of gait analysis data. Our hypothesis is that the hip and ankle joints are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Our results suggested a positive correlation between hip ROM and step length, stride length, and gait speed, but only the correlation with gait speed was statistically significant. One study showed that knee arthrodesis appeared to reduce knee ROM, resulting in decreased gait speed, step length, and stride length [ 27 ], but the findings were not statistically significant. Doyo et al [ 28 ] found that gait speed decreased with age, and that gait speed for females was higher than that for males.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested a positive correlation between hip ROM and step length, stride length, and gait speed, but only the correlation with gait speed was statistically significant. One study showed that knee arthrodesis appeared to reduce knee ROM, resulting in decreased gait speed, step length, and stride length [ 27 ], but the findings were not statistically significant. Doyo et al [ 28 ] found that gait speed decreased with age, and that gait speed for females was higher than that for males.…”
Section: Discussionmentioning
confidence: 99%
“…An arthrodesis of the knee alters the gait and the biomechanics of the hip. Walking speed is affected, and range of motion (ROM) reduced (especially the extension moment of the hip) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%